Effects of the Contemporary Economic and Financial Crisis on the Public Finances of Member Countries of the European Union - 27 - Rumenov, Deyan (Research Papers, 2014)
The contemporary financial and economic crisis highlighted the problem of high public indebtedness. Although the origin of the crisis was in the USA, there was a deterioration in the macroeconomic variables of the member countries of EU-27.This study examines the direction of the influence of the contemporary crisis on public revenues, public expenditures and public indebtedness of member countries of the EU-27. The examined period is divided in two parts – the first one, T1, spans over the years 2001 to 2007 and the second one, T2, spans over the years 2007 to 2012. A comparison is made of the dynamic of the public revenues, public expenditures, public debt, the indicators range and standard deviation of the macroeconomic variables for the two periods.The results from the study show that after the year 2007, as a rule there is an increase in the average public indebtedness of the member countries of EU-27, slowdown in public revenues for all member countries of EU-27 and an average slowdown in public revenues that is greater than the average slowdown in public expenditures.